Influence of social media on in-school adolescents’ morals : implication for school counsellors - Foluke. N, Bolu-Steve; Modupe. O, Omotayo; Alfred. A, Adegoke; Alfred. O, Awoyemi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Exposure to wrong content on social media could negatively influence adolescents’ moral development. This study, therefore, investigated the influence of Social Media on in-school adolescents’ morals in Ekiti State, Nigeria. The descriptive survey design was employed in this study. The population comprised all secondary school students in Ekiti State Nigeria. A multi-stage sampling technique was used to select 420 respondents for the study. Data were collected using a self-designed instrument tagged Social Media and Adolescents’ Morals Questionnaire (SMAMQ). Content validity of the instrument was ascertained and the reliability coefficient of 0.87 was obtained to ensure consistency of the instrument. Data analysis was done using percentages, t-test and Analysis of Variance (ANOVA). The findings of the study revealed that exposure of students to explicit sexual images or messages on social media influenced in-school adolescents’ morals in Ekiti State. Thus, the majority of the respondents indicated that social media influenced adolescents’ morals. The results further showed no significant difference in the influence of social media on in-school adolescents’ morals based on gender, school system, school type and location. This shows most adolescents use social media negatively. Thus, it was recommended that school counsellors should properly guide and mentor in school adolescents to take good advantage of social media for moral development.